Framing Pemberitaan Citra Politik Capres 2014 di Harian Solopos - Astutik, Puji Widi (Jurnal The Messenger, 2015)
The article tries to find out the construction of the image formation in the daily Solopos 2014 candidates. Basic theoretically in this paper uses descriptive analysis method with a form of text analysis models Zhongdang Pan and Gerald M. Kosicki through four units of analysis, syntax, script, thematic, and Rhetorical. Framing analysis is used to see how the image formation through the political news in the Daily Solopos 2014 candidates. Through this analysis can be found that the construction of a shadow image (mirror image) performed on the outlook for both candidates figure formed by the track record of each kandindat. Joko Widodo figure in the frame with the figure of the fight for the people and work for the people, while the figure Prabowo has a bad track record as it is considered to participate in the abduction tragedy in which 98 activists at that time as a military Prabowo.